GEOPHYSICAL TOMOGRAPHY: CURRENT STATE AND IMPLICATIONS FOR THE PETROLEUM GEOLOGY INDUSTRY - Troinich, K.; Matviychuk, B.; Vyzhva, S. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
This paper reviews current approaches to the implementation of the method of seismic tomography – a powerful tool which is used for solving the inverse problem in geophysics. Emphasis is laid on the application of geophysical tomography in the oil and gas industry at all field explortation and production stages. It has been shown that this method can be successfully used for the inversion of elastic and electrical parameters, anisotropy, etc. The threedimensional distribution of geophysical parameters in the explored medium obtained through imaging can be used to determine the geological (lithological) parameters such as mineral composition, structural and textural features, porosity, and fracture. A possible implementation of the inversion suggested is not into geophysical but directly into lithological parameters. It has also been demonstrated that tomography can be used to interpolate the well logging data in the inter-well space.